2018
DOI: 10.3390/su10093191
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Circular Economy Practices and Performance Among Romanian Producers

Abstract: Economic growth is the mandate of the global economy and with our planet’s population poised to reach 10 billion people, economists are searching for sustainable economic growth approaches that do not increase raw materials consumption nor deplete and damage our environment. This mandate is the heart of the Circular Economy (CE), a challenge to theoreticians and practitioners alike to continue global economic growth, but with fewer resources and protective methods for our environment. The European Union (EU) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 71 publications
(102 reference statements)
3
37
0
Order By: Relevance
“…Yuksel and Dagdeviren (2010), integrated BSC (Balanced Scorecard) approach, which is a method of determining business performance using indicators on the basis of vision and strategies, with fuzzy ANP technique to determine the performance level of a business in the manufacturing industry. Botezat et al (2018) showed that in the case of Romanian producers, the practices related to "green purchasing" and "customer cooperation" significantly determine the level of companies' performance. Hategan and Curea-Pitorac (2017), used as non-financial indicators the number of employees, the listed period and the ownership structure of the companies (private or state owed).…”
Section: Nonfinancial Indicatorsmentioning
confidence: 99%
“…Yuksel and Dagdeviren (2010), integrated BSC (Balanced Scorecard) approach, which is a method of determining business performance using indicators on the basis of vision and strategies, with fuzzy ANP technique to determine the performance level of a business in the manufacturing industry. Botezat et al (2018) showed that in the case of Romanian producers, the practices related to "green purchasing" and "customer cooperation" significantly determine the level of companies' performance. Hategan and Curea-Pitorac (2017), used as non-financial indicators the number of employees, the listed period and the ownership structure of the companies (private or state owed).…”
Section: Nonfinancial Indicatorsmentioning
confidence: 99%
“…In the first step of construction of the CE index, each indicator was categorized as one with a positive or negative impact on the index. For variables with a positive impact, values were transformed as in Equation (1) [44,45,53]:…”
Section: Construction Of the Ce Indexmentioning
confidence: 99%
“…There are a few studies proposing frameworks for transition to the circular economy model based on various incentives and instruments [51][52][53], but there is a lack of a system of indicators for evaluation and monitoring of CE progress at the regional level. Thus the main purpose of the current research was proposing a possible system of such regional level CE evaluation indicators.…”
Section: Introductionmentioning
confidence: 99%
“…If a new style of governance were adopted to continue cooperation, networking and improving value chain specialization as a result of regional policy motivation, if there were networks of companies leading up to the bottom to top clustering and focus on innovative management and learning processes, the transition of Romanian producers to EU requirements could be facilitated. But in the absence of concrete measures of this kind, the Romanian producers are in danger of failing to cope with the transition difficulties imposed by the EU legislation, and finally, the Romanian companies can be excluded from the European market by competitive pressures (Botezat, 2018). It seems that there are specialists in this area because Romania has developed innovative approaches with other countries, such as the "Green Laboratory of Recycling 2012 initiative that received the Gold Medal for Excellence in the SME category as part of the European Corporate Social Responsibility Award (CSR)".…”
Section: Aementioning
confidence: 99%